The image of the manager-leader of the near future - an outline of the issues - Glinkowska Beata; Kaczmarek Bogusław (Management, 2017)
The study contains description characteristics and analyses (obviously abbreviated) of two approaches and two concepts of management regarding the manager-leader of the near future. The first concept refers to new tasks and skills of the manager-leader. The second concept concerns the nature of the so-called manager of tomorrow, called - although it is not yet common name in management - the manager - eco-leader. In the introduction a reference was made to the issue raised, the purpose of the study, and the justification for choosing the concepts assumed in the study. In the next section, new tasks and skills of the manager - leader of the near future are cited and analyzed. The issues surrounding the concept of eco-leader were also discussed.